2018
DOI: 10.1007/s11356-018-3878-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental efficiency of Saccharomyces cerevisiae on methane production in dairy and beef cattle via a meta-analysis

Abstract: The objective of the present study is to examine the effect of yeast (Saccharomyces cerevisiae) on reduction of methane (CH 4 ) production in dairy and beef cattle using meta-analytic methods. After compilation of relevant scientific publications available from the literature between 1990 and 2016, and applying exclusion and inclusion criteria, meta-analyses of data from dairy and beef cattle were applied for the pooled dataset or for each animal category (dairy or beef). The results of meta-analysis of all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Diverse effects of yeast supplementation on CH 4 synthesis were attributed to varying yeast strains, dosages, and diets utilized in the trials [28]. Yeast can be used to minimize CH 4 emissions and was shown to lower methane production in the rumen by encouraging acetogens to use more hydrogen in the process of acetate formation by Darabighane et al [37]. In this study, the methanogen population was reduced with yeast supplementation and was lowest at 3 g/hd/d.…”
Section: Ruminal Volatile Fatty Acid (Vfa) Profiles and Methane (Ch 4 ) Productionmentioning
confidence: 57%
“…Diverse effects of yeast supplementation on CH 4 synthesis were attributed to varying yeast strains, dosages, and diets utilized in the trials [28]. Yeast can be used to minimize CH 4 emissions and was shown to lower methane production in the rumen by encouraging acetogens to use more hydrogen in the process of acetate formation by Darabighane et al [37]. In this study, the methanogen population was reduced with yeast supplementation and was lowest at 3 g/hd/d.…”
Section: Ruminal Volatile Fatty Acid (Vfa) Profiles and Methane (Ch 4 ) Productionmentioning
confidence: 57%
“…Additionally, inclusion of either a dead or live form of S. cerevisiae has little to no impact on nutrient digestibility or rumen fermentation patterns in beef heifers (Vyas et al 2014). A meta-analysis by Darabighane et al (2019) using data from 1990-2016 observed no significant reduction in CH 4 production through the use of probiotics.…”
Section: Probioticsmentioning
confidence: 99%
“…There are several strategies for CH 4 mitigation from ruminants that have been reviewed (Martin et al ). Live‐cell yeast and yeast products have recently been proposed to mitigate CH4 and it has been shown to reduce methane production in the rumen by stimulating acetogens to consume more hydrogen for acetate production (Darabighane et al ). In a previous study, Wang et al () reported that red yeast rice ( Monascus purpureus ) reduced the production of methane in goats.…”
Section: Impact Of Feeding Single‐cell Fungi On Rumen Fermentation Acmentioning
confidence: 99%